A Cooperative Diversity-Based Opportunistic Virtual MISO (OVM) Protocol for Multi-Hop Wireless Networks - Nguyen, Van; Perkins, Dmitri; Obeng, Morrison (International Journal of Sensors Wireless Communications and Control, 2011)
Wireless communications are highly error-prone due to inherent wireless channel effects, which include interference, multi-path fading, and noise. The conventional approach to reducing the effects of frequent channel errors is to attempt retransmitting the corrupted frames. This solution however introduces long end-to-end delay and channel usage inefficiency, especially in multi-hop wireless networks. In this work, we introduce the cooperative diversity-based opportunistic virtual MISO (Multiple-Input-Multiple-Output) approach to alleviate the problem and to improve the overall performance in multi-hop wireless networks. Our approach allows neighboring nodes to effectively share their available resources when there is an opportunity to participate. Our observation showed that multi-hop wireless networks consist of low and high quality links. In the low-quality links, we utilize spatial-diversity property that allows a wireless node with the highest delivery probability to relay data frames to the next hop. In the high-quality links, when there is more than one node successfully receiving the same data frame, we utilize space-time block codes (STBC) to extend the transmission range to deliver data frames up to two hops away. By proposing the approach described above, available network resources are always utilized to improve the overall performance. OVM provides an effective and simple design solution. Simulation results show that OVM is able to improve end-to-end network performance by up to eighty-six percent over previous works.
Keywords: cooperative diversity